The Influence of Work Culture and Civil Servant Discipline on Improving Performance at the Gorontalo City Finance Agency Office - Salsabila Muslim; Rusli Isa; Yacob Noho Nani (Universitas Negeri Gorontalo, 2026)
The results of the study show that (1) Work culture has a positive and significant effect on the discipline of employees at the Gorontalo City Financial Agency Office. A positive and significant effect means that the better the work culture in the system, the more disciplined the employees will be in carrying out their duties and functions as employees at the Gorontalo City Financial Agency Office. (2) Work culture has a positive and significant effect on improving employee performance at the Gorontalo City Financial Agency Office. A positive and significant effect means that the better the employee work culture, the better the employee performance achievement will be at the Gorontalo City Financial Agency Office. (3) Apparatus discipline has a positive and significant effect on improving employee performance at the Gorontalo City Financial Agency Office. A positive and significant effect means that the more disciplined employees are in carrying out their work safely, the more beneficial it will be in improving employee performance at the Gorontalo City Financial Agency Office. (4) Work culture through apparatus discipline has a positive and significant effect on improving employee performance at the Gorontalo City Financial Agency Office. A significant influence means that employee work discipline is a good intervening variable, namely being able to increase the benefits of work culture in stimulating employee performance at the Gorontalo City Finance Agency Office to experience improvements in a better direction.